Acute onset bilateral hearing loss in dorsomedial pontine hemorrhage: A Case report. Issue 34 (August 2019) - Hoshino, Masashi; Akiyama, Hisanao; Kashima, Satoru; Soga, Kaima; Shimizu, Takahiro; Hasegawa, Yasuhiro
Abstract: Rationale: Nontraumatic pontine hemorrhage represents approximately 10% of all cases of nontraumatic intracranial hemorrhage. The predominant cause and symptom of pontine hemorrhage are hypertension and disturbance of consciousness, respectively. Patient concerns: A 64-year-old man was transported to hospital by ambulance for sudden articulation disorder and right leg paralysis. He was neurologically alert with mild dysarthria, right leg paralysis, and increased deep tendon reflex in all limbs. Diagnosis: Plain head computed tomography showed an approximately 1.5 mL hemorrhage in the dorsomedial pons. Intervention: He was admitted to the Stroke Care Unit and received antihypertensive therapy. Outcomes: Around the time of admission, bilateral hearing loss suddenly developed with poorly defined wave V shown bilaterally on auditory brainstem response testing. As the hematoma subsequently resolved, the bilateral hearing loss recovered sufficiently to enable everyday conversation. Lessons: We report herein a rare case of acute onset bilateral hearing loss caused by nontraumatic pontine hemorrhage. Pontine hemorrhage is often associated with disturbance of consciousness; however, care is required as latent communication disorder due to impaired hearing is possible regardless of the state of consciousness.